Nontoxic, biodegradable hyperbranched poly(β-amino ester)s for efficient siRNA delivery and gene silencing - Ooi, Ying Jie (2024)
RNA interference (RNAi)-mediated gene silencing is a promising therapeutic approach to treat various diseases, but safe and efficient delivery remains a major challenge to its clinical application. Non-viral gene vectors, such as poly(β-amino esters) (pBAEs), have emerged as a potential candidate due to their biodegradability, low toxicity profile, ease of synthesis, and high gene transfection efficiency for both DNA and siRNA delivery. However, achieving significant gene silencing using pBAEs often requires a large amount of polymer carrier (with polymer/siRNA weight ratio >100) or high siRNA dose (>100 nM), which might potentially exacerbate toxicity concerns during delivery. To overcome these barriers, we designed and optimized a series of hyperbranched pBAEs capable of efficiently condensing siRNA and achieving excellent silencing efficiency at a lower polymer/siRNA weight ratio (w/w) and siRNA dose. Through modulation of monomer combinations and branching density, we identified the top-performing hyperbranched pBAEs, named as h(A2B3)-1, which possess good siRNA condensation ability, low cytotoxicity, and high cellular uptake efficiency. Compared with Lipofectamine 2000, h(A2B3)-1 achieved lower cytotoxicity and higher siRNA silencing efficiency in HeLa cells at a polymer/siRNA weight ratio of 30 and 30 nM siRNA dose. Notably, h(A2B3)-1 enhanced the gene uptake in primary neural cells and effectively silenced the target gene in hard-to-transfect primary cortical neurons and oligodendrocyte progenitor cells, with gene knockdown efficiencies of 34.8 and 53.4% respectively. By incorporating a bioreducible disulfide compartment into the polymer backbone, the cytocompatibility of the h(A2B3)-1 was greatly enhanced while maintaining their good transfection efficiency. Together, the low cytotoxicity and high siRNA transfection efficiency of hyperbranched h(A2B3)-1 in this study demonstrated their great potential as a non-viral gene vector for efficient siRNA delivery and RNAi-mediated gene silencing. This provides valuable insight into the future development of safe and efficient non-viral siRNA delivery systems as well as their translation into clinical applications.